Between the lines: A mixed-methods study on the impacts of parental deportation on the health and well-being of U.S. citizen children - Ana Martinez-Donate; M. Gudelia Rangel; Jamile Tellez Lieberman; J. Eduardo Gonzalez-Fagoaga; Catalina Amuedo-Dorantes; Elizabeth McGhee Hassrick; Carmen Valdez; Kevin Wagner; Yosselin Turcios; Ahmed Asadi Gonzalez; Xiao Zhang (Elsevier, 2024)
Objective: To explore the impacts of parental deportation on the health and well-being of U.S. citizen children of Mexican immigrants. Methods: From 2019-2020, this ambi-directional cohort study recruited U.S.-based families with an undocumented Mexican immigrant parent and U.S.-citizen childrens (ages 13-17) recently exposed to parental deportation (N = 61), and similar families without a history of parental deportation (N = 51). Children health, behavioral, economic, and academic outcomes were measured via phone surveys upon enrollment and six months later. A subsample of "exposed" caregivers (N = 14) also completed in-depth semi-structured interviews. Data were analyzed using fixed-effects regression models and thematic analyses. Results: Childrens exposed to parental deportation had significantly worse health status, behavioral problems, material hardship, and academic outcomes than children in the control arm (p<.05). Caregivers' interviews illustrated these health, behavioral, academic and family impacts. Conclusions: Parental deportations have wide and potentially long-lasting health, behavioral, economic, and academic consequences for U.S. citizen youth. Changes in immigration policies and enforcement practices are urgently needed to protect the unity of mixed-legal status families in the U.S. and prevent the suffering of U.S. children in these families.